Conceptual Framework of Environmental, Social, and Governance (ESG) Research: Trends, Themes, and Emerging Perspectives - Mohamad Yazis Ali Basah; Ainulashikin Marzuki; Nur Ainna Ramli; Fauzias Mat Nor; Muhammad Ridhwan Ab. Aziz; Syahidawati Hj. Shahwan; Hisham Sabri (Penerbit USIM, 2024)
The Journal of Muamalat and Islamic Finance Research Volume: 21 No: 2 (page: 17-36)